The Effect of Liquidity on Tax Avoidance with Profitability Mediation Variable in BUMN Companies Listed on The IDX in 2017-2018 - Marito, Jojor Sihol; Hutabarat, Francis (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2020)
The research objective was to determine the effect of liquidity on tax avoidance with profitability mediation variable in bumn companies listed on the idx in 2017-2018. This study uses a descriptive method with a population of 20 companies and uses a sample of 40 research samples based on 20 BUMN companies listed on the Indonesia Stock Exchange for the year 2017-2018 period. Analysis of the data is the coefficient of determination, F test, t-test, multiple regression. The significant test results show that in model 1 there is no significant effect between liquidity and tax avoidance, this is evidenced by the F-test 4.089 and a significant value of 0.05 at Î± = 5%. Whereas in model 2, it is found that with the mediation of profitability it is found that the effect of liquidity, profitability on tax avoidance is significant with a significant level of 0.032 at a significant level of 5% with an F-test of 3.779.The significant test results show that the independent variable shows that in model 1 there is no significant effect on the liquidity variable on tax avoidance with a significant value of 0.50 at the 10% significant level. Whereas in model 2, it is found that there is a mediation of profitability, it is found that liquidity and tax avoidance have a significant effect, namely 0.060 at a significant level of 10%. And related to profitability and tax avoidance, there is a significant effect with a significant level of 0.080 at a significant level of 10%. Thus, the existence of profitability does partially mediate the effects of liquidity and tax avoidance. So it is concluded that liquidity has a significant effect on tax avoidance, and profitability has a significant effect on tax avoidance.